PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN KELENG KAPAN MENGAJAR MELALUI IN-HOUSE TRAINING YANG BERMUARA KEPADA HIGHER ORDER THINKING SKILLS/ HOTS PADA SD. NEGERI 136537 TANJUNGBALAI TAHUN PALAJARAN 2021/2022 - Mailina Mailina (Universitas Dharmawangsa, 2021)
This School Action Research (PTS) aims to prove scientifically whether in-house training (IHT) coaching and training can improve teacher competence in compiling Higher Order Thinking Skills (HOTS) assessments. The method used in this study is the School Action Research (PTS) method. The study subjects were state elementary school teachers 136537 the Nibung Bay Of Tanjungbalai City, with the number of teachers as many as 8 (eight) people. The data collection techniques used are observation techniques, interviews. This research was conducted 2 cycles, namely the first cycle carried out by the guidance method, based on the above discussion there was an increase in teacher competence in compiling HOTS assessments. In cycle I the average value of the HOTS assessment component is 12.5%, in cycle II the average value of the HOTS assessment component becomes 100%, there is an increase of 87.5% and the success indicator is exceeded which is 78.00%. This means that through coaching and training can be.